Rekam Jejak Kinerja Crew Sebagai Model Sistem Pendukung Keputusan Pengangkatan Leader - Thanri, Yan Yang (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Competitive human resources are employees who can work productively and professionally to achieve the vision, mission and goals of the company. To get competitive human resources seen from the quality of the employee's performance. The quality of employee performance is recorded in the track record of employee performance that has an important role for the company in making decisions in improving the company's human resources. North Sumatra, in particular the city of Medan, many companies engaged in the family entertainment center, the results of observations that have been made to several companies engaged in this field, generally in terms of appointment of Leaders still use the seniority system and spoil system. The impact of the seniority system is not guaranteeing the competency of an employee and not necessarily being able to assume the position, the impact of the spoil system is promotion based on kinship, this system is not good because it is based on consideration of likes or dislikes. To overcome the above, we need a system of track record of crew performance as a model of decision support systems for the appointment of leaders by involving factors of merit system, seniority system and leadership. The decision support system model will use the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods. AHP is a method that will be used to make comparisons between criteria to get criteria weights while SAW is a method used to find the weighted sum of the results of the AHP method of rating performance on all alternatives of each attribute to provide recommendations for company leaders to make the selection of the crew and conduct the process of appointing a Leader.